2020
DOI: 10.1101/2020.05.15.20103135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Management of large polyps in a colorectal cancer screening program with fecal immunochemical test: a population-based study

Abstract: Objective: To analyse presentation, management and outcomes of large (≥ 20 mm) polyps (LPs) detected in a colorectal cancer (CRC) screening programme using a faecal immunochemical test (FIT) and to compare them with those of a previous guaiac-based faecal occult blood test (gFOBT) programme. Design: Retrospective population-based study of all LPs detected in patients aged 50-74 years between 2015 and 2019 during FIT-positive colonoscopies within the screening programme organised in Alsace (France). Results: Ov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We proposed elsewhere a new indicator to evaluate the latter and demonstrated that detection and polypectomy competency were correlated. 46 And finally, the endoscopist’s ADR should be considered for determining the post-polypectomy surveillance schedule in order to address the paradox that the shortest surveillance intervals are recommended by endoscopists with the highest ADRs, and inversely. Today, none of the existing recommendations take into account the endoscopist’s ADR for the determination of the post-polypectomy surveillance schedule.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed elsewhere a new indicator to evaluate the latter and demonstrated that detection and polypectomy competency were correlated. 46 And finally, the endoscopist’s ADR should be considered for determining the post-polypectomy surveillance schedule in order to address the paradox that the shortest surveillance intervals are recommended by endoscopists with the highest ADRs, and inversely. Today, none of the existing recommendations take into account the endoscopist’s ADR for the determination of the post-polypectomy surveillance schedule.…”
Section: Discussionmentioning
confidence: 99%